Data relating to: "Identifying challenges in quantifying uncertainty: case study in infrared thermography" (2018) - Grenyer, Alex; Addepalli, Pavan; Zhao, Yifan; Oakey, Luke; ahmet Erkoyuncu, John; Roy, Rajkumar (Cranfield University, 2020)
Excel file corresponding to data in conference paper:'Paper tables' tab contains summary of variables used in the paper, calculated using MATLAB 'Conditions' tab contains recorded temperatures and humidity for each run read by MATLAB 'Readings' tab collates reading values for each run read by MATLAB'Run1-10' tabs contain data recorded for each run including ROI size and locationPowerPoint file: Conference presentation
Keywords: 'Uncertainty Quantification'; 'Challenges'; 'Industrial product service system'; 'Complex engineering system'; 'Thermography'; 'Statistics'; 'Manufacturing Engineering not elsewhere classified'